Perencanaan Komunikasi Badan Perencanaan Pembangunan Daerah dalam Pelaksanaan Program SDGS di Kabupaten Pangkep - Muhammad Ilham (Journal of Communication Sciences (JCoS), 2019)
Communication planning in the implementation of development becomes a guide in implementing development activities programs such as the implementation of the Sustainable Development Goals Program (SDGs). As one of the central government programs embodied in the concept of sustainable development in Indonesia and the regions as the spearhead, the authors examine the communication planning activities of the Pangkep Regency Regional Development Planning Agency as the leading Sector in the implementation of the SDGs program in Pangkep Regency. This study uses qualitative research methods, which attempt to describe the object under study in the field. The data obtained through interviews, observations and collaborated documentation show the results, namely that the Bappeda Pangkep has carried out communication planning based on the strength of the source, processing messages, use of media or channels as well as determining the target of adoption or recipient.